(untitled) (ESMAT Magazine, 2018)
Poverty presents a problem in terms of its definition. The standards that measure it vary from region to region. However, poverty is a multifactorial phenomenon that translates into the lack of goods and services necessary for subsistence. The fundamental rights that serve to eradicate poverty are classified within economic, social and cultural rights. They usually refer to the right to work, social security, housing, a healthy environment, family, education, water and food. The Mexican legal system has a double protection and guarantee for this type of rights: in the national law, constitutional articles 4, 5 and 123 recognize them and guarantee them through the ‘amparo’ figure; while in international law, Mexico signed the American Convention on Human Rights and the Protocol of San Salvador, which regulates economic, social and cultural rights. These are guaranteed by the procedures provided for at the Inter-American Human Rights System.